Baa-iov: Blockchain-enabled anonymous authentication for internet of vehicles - Wenfeng Huang; Si Chen (PLoS ONE, 2026)
As a core component of intelligent transportation systems, the Internet of Vehicles (IoV) relies heavily on secure and efficient authentication mechanisms to support real-time information exchange and data sharing among network entities. However, traditional centralized authentication schemes widely adopted in current IoV systems suffer from several drawbacks, including performance bottlenecks, inefficient cross-domain authentication, and insufficient identity privacy protection, which severely restrict the security and scalable deployment of IoV systems. To address these challenges, this paper proposes a novel blockchain-based multi-Trusted Authority (TA) collaborative authentication and key agreement scheme. The scheme adopts a decentralized cross-TA authentication architecture based on blockchain-enabled trust transfer to eliminate single point of failure risks. Furthermore, it constructs an anonymous authentication protocol supporting both vehicle-to-TA and vehicle-to-vehicle key agreement, ensuring identity privacy and resisting various security attacks. Comprehensive security validation, including Burrows-Abadi-Needham (BAN) logic formal analysis, informal security verification, and ProVerif-based verification, confirms the scheme’s strong security guarantees. Comparative evaluations with existing schemes demonstrate that the proposed scheme achieves reasonable energy consumption while ensuring high security performance. Specifically, its computational cost is reduced by 39.42% compared with the best existing scheme.